The role of MYB in MLL-AF9 leukaemia - Lau, IJ (2019)
MYB is a DNA-binding transcription factor with a critical role in the establishment of definitive haematopoiesis. In haematological malignancies, MYB is a direct downstream target common to several MLL-fusion proteins (MLL-FP), including MLL-AF9, the most common MLL-FP in acute myeloid leukaemia. MYB is necessary for the maintenance of MLL-AF9 leukaemia, and even partial and transient loss of MYB has been shown to abrogate MLL-AF9 leukaemia in vivo. While MYB inhibition is able to attenuate leukaemogenesis, its specific requirement in the processes of leukaemia initiation and transformation is still unclear. Furthermore, despite its obvious importance in normal and malignant haematopoiesis, much is still unknown regarding its molecular function. Recent evidence from disease models suggests that MYB functions through establishing aberrant enhancer activity, however this hypothesis has yet to be rigorously tested. In this thesis, to investigate the requirement for MYB in leukaemia initiation, we engineered a conditional miRNA mediated Myb repression circuit in a mouse model system, which represses Myb only in the presence of the MLL-AF9 oncoprotein. Myb repression during leukaemia initiation was correlated with a trend in decreased clonogenic potential in vitro, as well as a convincing reduction in leukaemia fitness in vivo, suggesting that a threshold level of Myb is required to propagate an aggressive leukaemia phenotype. Using an artificial chromatin recruitment system, we demonstrated that the MYB transcriptional activation domain was sufficient to generate an enhancer-like element and induce transcription of distal sequences, suggesting that MYB may be competent to initiate enhancer activity in vivo. Further to this, weshowed that MYB dependent gene activation appears to be mediated through its maintenance of enhancer activity, as demonstrated by the loss of H3K27ac, enhancer RNA transcription and chromatin accessibility at the cognate intergenic enhancers of specific MYB sensitive genes with MYB knockdown. Importantly, we found that MYB dependent gene activation can be disrupted with minimal changes in enhancer-promoter interaction frequency, suggesting that these are functionally and temporally separable events.